134k views
4 votes
Question attached as photo​

Question attached as photo​-example-1
User Hmmm
by
5.2k points

1 Answer

3 votes

Answer:

2)
(1)/(\sqrt[6]m^(5))

Explanation:

As per the laws of indices:


(x^(a) )/(x^(b) ) = x^(a - b) \\\\and \\ \\(x^(a))^b = x^(ab)

Therefore:

2-(1/3) = 5/3

So m ^(5/3)

5/3 multiplied by -1/2 = -5/6

so m^(-5/6)

Another law of indices:


x^{(a)/(y) } = \sqrt[y]{x^(a) } and when there is something raised to a negative fraction do the reciprocal.

User Vijay Chauhan
by
5.9k points